2021
DOI: 10.1177/03400352211054115
|View full text |Cite
|
Sign up to set email alerts
|

‘The challenge now is for us to remain relevant’: Australian public libraries and the COVID-19 crisis

Abstract: The COVID-19 crisis has had a significant impact on public libraries around the world. In Australia, almost all public libraries experienced some period of building closure, requiring libraries to adapt their services and delivery models. This article reports findings from a large-scale survey of public library managers in Australia, which was conducted in August 2020. In particular, it presents the results of a thematic analysis of the participants’ free-text responses to open questions asked as part of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In addition to these insights into managerial practices, the findings from this research also speak to another key element of public libraries' response to the COVID-19 crisis: the emphasis placed on the welfare of community members. We have addressed this element in other publications (Randell-Moon et al, in press;Wakeling et al, 2022), but the interview data reported in this paper speak to the operations side of this phenomenon. Managers described an awareness of the fact that some library users' inability to access online services and resources might mean a sudden loss of contact with the library, and recognised the Australian public libraries during COVID-19 consequences of this at time when risk of isolation was highest.…”
Section: Communicationmentioning
confidence: 76%
See 3 more Smart Citations
“…In addition to these insights into managerial practices, the findings from this research also speak to another key element of public libraries' response to the COVID-19 crisis: the emphasis placed on the welfare of community members. We have addressed this element in other publications (Randell-Moon et al, in press;Wakeling et al, 2022), but the interview data reported in this paper speak to the operations side of this phenomenon. Managers described an awareness of the fact that some library users' inability to access online services and resources might mean a sudden loss of contact with the library, and recognised the Australian public libraries during COVID-19 consequences of this at time when risk of isolation was highest.…”
Section: Communicationmentioning
confidence: 76%
“…As has been widely acknowledged, Australian public libraries responded to the pandemic, and particularly the closure of library buildings, with great agility (Smith, 2020;Wakeling et al, 2022). A key issue articulated by many of our participants was the constant changing of regulations and public health requirements, which in many cases were implemented at extremely short notice.…”
Section: Flexibilitymentioning
confidence: 92%
See 2 more Smart Citations
“…Whilst the spread of the pandemic impaired the libraries' ability to establish a continuous interplay with the community and to advance the individual and collective access to timely and trustworthy information (Alajmi and Albudaiwi, 2021), technological advancements (Asif and Singh, 2020) and management innovations (Ameen, 2021) enabled libraries to preserve their public value generation capability. Digitization, flexibility and adaptability have been widely depicted as the cornerstones on which libraries' viability relies (Wakeling et al, 2022;Yu et al, 2022). However, literature is not consistent in arguing which innovations are most effective to match the evolving needs and expectations of the audience (Ali et al, 2021;Antunes et al, 2021), augmenting the libraries' organizational attractiveness (Palumbo, 2022).…”
Section: Conceptual Backgroundmentioning
confidence: 99%